Efectos de la musicoterapia y aromaterapia en pacientes que asisten a consulta odontológica. Revisión de literatura. (2021)
In dental care, the need to manage anxiety in some patients who request the provision of these services has been evidenced and this is how since the 50's different academic disciplines in Universities, specialized centers and organizations have begun to investigate and take importance, over time studies have increased that refer to interventions that use music therapy and aromatherapy as tools that can contribute to a more pleasant care for individuals who request dental services.